Optimization and enzymatic hydrolysis of Tilapia by-product and fractionation of protein hydrolysate using membrane ultrafiltration - Roslan, Jumardi (2016)
Large amount of by-products is generated during tilapia processing, including skins, bones, frames and tails. The conversion of fish by-products through enzymatic hydrolysis is the most promising alternative in order to produce a valuable products such as fish protein hydrolysate (FPH) which rich in an essential nutrients and bioactive peptides that offer physiological functions, such as antihypertensive activity. FPH consists of peptide mixtures with various sizes, there is a need for separate them using ltrafiltration (UF) membrane in order to improve yield and obtain a specific size of peptide which closely related to the high potent of antihypertensive activity. Therefore, this research is focused on the production of a small-sized bioactive peptide from tilapia by-product which responsible for angiotensin I-converting enzyme (ACE) inhibitory activity through enzymatic hydrolysis and membrane fractionation process. This study has three main objectives (1) to optimize the parameters for improvement of enzymatic hydrolysis of tilapia by-products using response surface methodology in order to achieve high degree of hydrolysis (DH), (2) to characterize the protein hydrolysates from enzymatic hydrolysis of tilapia by-product emphasizing on ACE inhibitory activity, chemical composition and functional properties, and (3) to evaluate the performances of the single and multilayer membranes for the fractionation of tilapia’s by-product protein hydrolysate, in order to enrich the peptide with a high ACE inhibitory activity.The optimization of enzymatic hydrolysis using alcalase for preparing the tilapia muscle’s (TM) and by-product (TB) protein hydrolysates were performed through a response surface methodology (RSM). The O-phtaldialdehyde (OPA) method was employed to measure the degree of hydrolysis (DH). The optimum enzymatic hydrolysis conditions for the TM was obtained at pH 7.5, temperature of 50 ,substrate concentration of 2.5% (w/v) and enzyme concentration of 95.6 (AU/kg protein) with DH value is 25.41%. For TB, the highest DH was achieved at 20.42% with the optimum conditions at pH 7.5, temperature at 60 , substrate concentration of 15% (w/v) and 60.2 (AU/kg protein) of enzyme concentration. Under these optimum conditions, the TM and TB protein hydrolysates were further hydrolyzed for 30-720 minutes to investigate the highest ACE-inhibitory activity could be achieved. The highest ACE-inhibitory activities was achieved at 1 hour of hydrolysis and selected for the next analysis such as peptide size distribution, chemical compositions, physical appearance and functional properties. It was found that both samples have various sizes of low molecular peptides ranging from 1.06 to 26.6 kDa.TM and TB protein hydrolysates have shown a good nutritional value with respect to high protein contents (36.55 and 65.64%, respectively) and essential amino acids such as lysine, leucine and threonine. The high amount of hydrophobic amino acids in both the TM and TB protein hydrolysates might contribute to high ACE-inhibitory activities.TM and TB protein hydrolysates were rich in mineral elements such sodium, phosphorus and potassium, indicating a potential of samples to be an alternative sources of mineral. From scanning electron microscopy result, smooth microstructures in aggregation packed flake-like structures formed with the broken structures in irregular and cracked particles,representing shorter peptide chain length were observed for both samples. The findings also demonstrated that TM and TB protein hydrolysate have high nitrogen solubility (>80% at pH 2-9), and possessed good water-holding capacity, and oil holding capacity.The fractionation of TB protein hydrolysate with the dead-end ultrafiltration (UF)membrane was investigated through single and multilayer membrane using a regenerated cellulose membrane with 10 and 5 kDa molecular weight cut off (MWCO). The performance of the fractionation using the single membrane (10 and 5 kDa) and multilayer membranes (10/5 and 5/5 kDa) were investigated through the effects of stirring speed (0-600 rpm), pH (3, 5, 7, 8 and 9) and salt concentration (NaCl; 0 M, 0.2 M, 0.4 M, and 0.6 M) on the flux and peptide transmission. The best fractionation process were found at the stirring speed of 600 rpm and pH 8 for both single and multilayer membranes which is based on the highest permeate flux and peptide transmission obtained. The permeate produced from each membrane were evaluated their ACE-inhibitory activity. For single membrane, it was found that 5 kDa membrane (71.83%) has higher ACE inhibitory activity compared to 10 kDa membrane (64.32%). Both permeates from multilayer membrane exhibited higher ACE inhibitory activity as compared to single membrane. It is proven that there is a relationship between peptide size and ACE inhibitory activity. Through a selectivity analysis using Fast Pressure Liquid Chromatography (FPLC), the most permeate produced were composed of peptides lower than 1500 Da. It was found that, fractionation using 10 kDa membrane produced more peptide with large size as compared to other membranes. The percentage of peptides with size less than 500 Da increased as the smaller membrane pore size used. More peptides with small size which is less than 500 Da were obtained for 5/5 kDa multilayer membrane indicating that the peptide selectivity of membrane can be improved through multilayer membrane. Overall, the conversion of tilapia by-products into fish protein hydrolysate has shown a great potential to be used in nutraceutical and pharmaceutical products which is based on the high ACE inihibitory activity obtained from enzymatic hydrolysis and membrane fractionation process.